(untitled) (Jurnal Bina Praja, 2023)
This study aims to explore the relationship between work values, work attitude, leadership style, and job performance from two generations, namely Gen X and Gen Y, in the Department of Health, Population and Civil Registration of East Nusa Tenggara Province. The sampling technique used convenience sampling through Google Forms and then sent to each employee. The population and sample in this study were 168 people, including 72 people from Generation X with birth years 1965-1980 and 96 people from Generation Y with birth years 1981-2001. Based on this number, only 124 questionnaires were filled out and returned to researchers, of which Generation X was 46 and Generation Y was 78. This study showed different results for the two generations; Gen Six hypotheses were accepted. Two hypotheses were rejected, including work values affecting work attitude but not on job performance, work attitude affecting job performance, and leadership style affecting work values but not job performance. Work attitude can mediate between work value and job performance; work values can mediate the influence between leadership style and work attitude and job performance. In Generation Y, six hypotheses were accepted, and two hypotheses were rejected, including work values influencing work attitude and job performance, work attitude does not influence job performance, and leadership style influencing work values and job performance. Apart from that, work attitude is not able to mediate between work value and job performance; work value can mediate the influence between leadership style and work attitude and job performance.